2020
DOI: 10.1016/j.heliyon.2020.e03400
|View full text |Cite
|
Sign up to set email alerts
|

Trivariate modelling of the nexus between electricity consumption, urbanization and economic growth in Nigeria: fresh insights from Maki Cointegration and causality tests

Abstract: In this era of intensive electricity utilization for economic development, the role of urbanization remains inconclusive, especially in developing economies. Here, this study examined the electricity consumption and economic growth nexus in a trivariate framework by incorporating urbanization as an additional variable. Using the recent novel Maki cointegration test, Ng-Perron, Zivot-Andrews, and Kwiatkowski unit root tests along with FMOLS, DOLS and the CCR estimation methods, we relied on an annual frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
46
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(60 citation statements)
references
References 84 publications
14
46
0
Order By: Relevance
“…As reported in Tables 7, 8, the result of ARDL methodology show that there is a positive and statistically significant relationship between GDP per capita and environmental degradation in case of Pakistan, thus signifying that the GDP per capita rises CO 2 e in the short-run as well as in the long-run. Particularly, the findings of this study are comparable with the work of Adedoyin et al (2020) for BRICS economies, Ali et al (2020) for Nigeria, Khan (2019) for ASEAN countries, Malik et al (2020) for Pakistan, Lu (2017) for developing countries, Usman et al (2020) for upper middle income countries (UMICs), and Zhang et al (2014) for China. From the empirical results of this study, we are able to conclude that the existing economic growth and economic activities in developing countries like Pakistan contribute to the reduction of extreme poverty but with high environmental costs in the shape of environmental degradation.…”
Section: Estimation Of Ardl Modelsupporting
confidence: 79%
“…As reported in Tables 7, 8, the result of ARDL methodology show that there is a positive and statistically significant relationship between GDP per capita and environmental degradation in case of Pakistan, thus signifying that the GDP per capita rises CO 2 e in the short-run as well as in the long-run. Particularly, the findings of this study are comparable with the work of Adedoyin et al (2020) for BRICS economies, Ali et al (2020) for Nigeria, Khan (2019) for ASEAN countries, Malik et al (2020) for Pakistan, Lu (2017) for developing countries, Usman et al (2020) for upper middle income countries (UMICs), and Zhang et al (2014) for China. From the empirical results of this study, we are able to conclude that the existing economic growth and economic activities in developing countries like Pakistan contribute to the reduction of extreme poverty but with high environmental costs in the shape of environmental degradation.…”
Section: Estimation Of Ardl Modelsupporting
confidence: 79%
“…Nguyen and Nguyen (2018) found that urbanization positively affects GDP in the ASEAN countries. Ali et al (2020a) examined the association between urbanization and GDP using the Maki cointegration test, FMOLS, DOLS, CCR, and VECM Granger causality covering the period from 1971 to 2014.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Additionally, With respect to electricity consumption, Mezghani and Haddad (2017) attempt to explore the interrelationship of Saudi Arabian real GDP (oil, nonoil), electricity consumption, and CO 2 emissions levels by employing the Time‐Varying Parameters Vector Autoregressive model with stochastic volatility and indicate that the variations in the volatility of oil GDP levels positively impact CO 2 emissions and electricity consumption. Additionally, Ali, Nathaniel, Uzuner, Bekun, and Sarkodie (2020) and Nathaniel and Bekun (2020) explore the nexus between electricity consumption, urbanization, and economic growth in Nigeria, and highlight the need for policies to ensure efficient electricity supply to promote sustainable economic growth. Additionally, with specific reference to the environment in Nigeria, Nathaniel (2019) also explores the link between urbanization, trade flow, energy consumption, and economic growth, and suggests policies for energy and poverty, for enhanced sustainable growth.…”
Section: Literature Reviewmentioning
confidence: 99%